Efficacy of neem plant products against the budfly (Dasineura lini ) on linseed (Linum usitatissimum) - GUPTA, M P; CHOURASIA, S K; RAI, H S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1996-99 to evaluate neem plant products against the infestation of budfly, (Dasineura lini Barnes) on linseed for three consecutive winter (rabi) seasons at Tikamgarh, Madhya Pradesh. The maggot infestation and capsule damage were minimum in phosphamidon 0.04% followed closely by neem oil 1 % and neem oil 0.5% treatments. Except NNG grain yield increased significantly in all the neem products and phosphamidon and was maximum in neem oil 1% treated plots (I 869 kg/ha) followed by phosphamidon (I 754 kg/ha) and neem oil 0.5% (1 750 kg/ha) as compared to control (1 332 kg/ ha). Maximum net profit was given by neem oil 1 % (Rs G 918) followedby phosphamidon 0.04% (Rs 5 428) and neem oil 0. 5% (Rs 5402). Whereas, leBR was highest in neem oil 0.5% (13.0) followed by neem oil 1 % (12.5) and phosphamidon (12.3). However, neem leaf extract and neem kernel extract seconded the neem oil in efficacy as well as in yield.